To the committees of the several towns and counties of the province of North-Carolina : appointed for the purpose of carrying into execution the resolves of the Continental Congress - Hooper, William, 1742-1790 ([Printed by James Davis?], 1775)
Circular letter, exhorting the people of North Carolina to awake to their present danger, and to train and equip a militia; signed and dated on p. [2]: William Hooper, Joseph Hewes, Richard Caswell. Philadelphia, June 19, 1775. Hooper, Hewes and Caswell were the delegates to the Continental Congress from North Carolina.